The Effect of Return on Asset (ROA) And Current Ratio (CR) on Stock Prices Through Green Accounting As an Intervening Variable In Syariah Stock Companies Listed in Jakarta Islamic Index Period 2019-2023 - Ramadhan, Muhammad; Batubara, Maryam; Rahmani, Nur Ahmadi Bi (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The ability of Islamic stock companies to generate profits, pay obligations and have a high ranking in environmental financing does not necessarily have the highest stock price. Therefore, a study was conducted with the aim of determining the effect of ROA and CR and green accounting on stock prices, to determine the effect of ROA and CR on stock prices through green accounting as an intervening variable in Islamic stock companies listed on JII for the 2019-2023 period. The population was 30 JII constituent companies. The research sample was 65 observations from 13 companies according to the criteria for 5 years of observation. The data analysis technique used panel data regression assisted by Eviews software version 10. The results of the study (1) ROA has a positive and significant effect on Green Accounting (2) CR has a positive but not significant effect on Green Accounting; (3) ROA has a positive and significant effect on Stock Price; (4) CR has a positive and significant effect on Stock Price; (5) Green Accounting has a negative but not significant effect on Stock Price; (6) ROA has a negative but not significant effect on stock prices through green accounting as an intervening variable; (7) ROA has a negative but insignificant effect on stock prices through green accounting as an intervening variable.